Historiografia americana em revista: a American Historical Review (1895 a 1915) - Perpétuo, César Haueisen Zimerer (2017)
The American Historical Review (AHR) was created in 1895 by a small group of intellectuals who, motivated by the emergence of several other periodicals in the XIX century, sought to create a new platform for all American historians to publish their Works and create new professional ties with their colleagues. In the AHR were published a series of reviews, documents, articles and other types of communications and texts that were responsible for facilitating the debate and the contact between historians and other intellectuals. In this dissertation, I intend to show how it is possible to carry out a deep analysis of the historiography of a certain period from the study of historical periodicals, taking as an example the first twenty years of existence of the American Historical Review, including its history, conjucture and mapping the published articles to find a pattern of key clippings, themes and objects of study that can show us the physiognomy of the AHR at that time.